Feminism and Pragmatism: Феминизмот и прагматизмот - Rorty, Richard; Dimiškovska-Trajanoska, Ana (Identities: Journal for Politics, Gender and Culture, 2001)
Author(s): Richard Rorty | Ричард Рорти Title (English): Feminism and Pragmatism Title (Macedonian): Феминизмот и прагматизмот Translated by (English to Macedonian): Ana Dimiškovska-Trajanoska | Ана Димишковска-Трајаноска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 187-226 Page Count: 40 Citation (English): Richard Rorty, “Feminism and Pragmatism,” Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001): 187-226. Citation (Macedonian): Ричард Рорти, „Феминизмот и прагматизмот“, превод од англиски Ана Димишковска-Трајаноска, Идентитети: списание за политика, род и култура, т. 1, бр. 1 (лето 2001): 187-226.